Preparation and Properties of Nanopolysaccharides - Lavoine, Nathalie; Durmaz, Ekrem; Trovagunta, Ramakrishna (Springer Singapore, 2019)
With the raising environmental awareness of the society, the interest in exploiting nanomaterials from renewable resources is rapidly increasing. Renewable nanotechnology not only features the outstanding properties of common synthetic nanomaterials, but also combines renewability, biodegradability and biocompatibility. These past two decades have seen the emergence of so-called nanopolysaccharides, namely nanoscale particles isolated and/or produced from renewable and abundant materials such as cellulose, chitin and starch. These particles are paving the way for the design of high-performance tailored materials, which can address the current environmental and sustainability concerns of our society. Their potential in replacing plastics from petroleum-based polymers is especially the key driver behind this global and raising research effort. This chapter introduces the different preparation routes and main properties of nanopolysaccharides from cellulose, chitin and starch; three of the most abundant biopolymers available and exploited today. This chapter suggests as well potential applications and usages for these nanoparticles, as a preamble of the following next chapters, which will illustrate much more in details how these nanoparticles can change our society of tomorrow.
Keywords: 13. Climate action; 7. Clean energy; 12. Responsible consumption